Anomalous Jahn–Teller behavior in a manganese-based mixed-phosphate cathode for sodium ion batteries. Issue 11 (28th September 2015) - Kim, Hyungsub; Yoon, Gabin; Park, Inchul; Park, Kyu-Young; Lee, Byungju; Kim, Jongsoon; Park, Young-Uk; Jung, Sung-Kyun; Lim, Hee-Dae; Ahn, Docheon; Lee, Seongsu; Kang, Kisuk
Abstract : We report a 3.8 V manganese-based mixed-phosphate cathode material for applications in sodium rechargeable batteries; i.e., Na4 Mn3 (PO4 )2 (P2 O7 ). Abstract : We report a 3.8 V manganese-based mixed-phosphate cathode material for applications in sodium rechargeable batteries; i.e., Na4 Mn3 (PO4 )2 (P2 O7 ). This material exhibits a largest Mn 2+ /Mn 3+ redox potential of 3.84 V vs. Na + /Na yet reported for a manganese-based cathode, together with the largest energy density of 416 W h kg −1 . We describe first-principles calculations and experimental results which show that three-dimensional Na diffusion pathways with low-activation-energy barriers enable the rapid sodium insertion and extraction at various states of charge of the Na4− x Mn3 (PO4 )2 (P2 O7 ) electrode (where x = 0, 1, 3). Furthermore, we show that the sodium ion mobility in this crystal structure is not decreased by the structural changes induced by Jahn–Teller distortion (Mn 3+ ), in contrast to most manganese-based electrodes, rather it is increased due to distortion, which opens up sodium diffusion channels. This feature stabilizes the material, providing high cycle stability and high power performance for sodium rechargeable batteries. The high voltage, large energy density, cycle stability and the use of low-cost Mn give Na4 Mn3 (PO4 )2 (P2 O7 ) significant potential for applications as a cathode material for large-scale Na-ion batteries.